Methodology For Improving Professional Training Of Future Physics Teachers Based On Subjective-Reflective Teaching Strategy (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This article provides information on the methodology of improving the professional training of future physics teachers based on the subjective-reflexive teaching strategy